Environmental Friendly Mineral Block - Siti Nurfadilah Arshad (Penerbit Universiti Malaysia Perlis, 2011)
Mineral block are common supplement food sources of ruminants animals that usually use by farmer. It can be found either in the wild or through solidification process. The aim of this study is to enhance utilization of these supplement food sources to small farmer and to reduce or eliminate the usage of cement in mineral block composition. Generally, in this study the mineral block were prepared from mixer of the mineral sources and built in block condition through solidification process. The mineral sources were characterized using characterization techniques. Then the mineral sources that stand by fermentable energy sources and fiber sources that come from agro-industrial byproduct were mixed with potato starch to form mineral block composition. These mineral block composition were further heated under controlled conditions to dry the moisture in the composition and to form gelatinization of starch to make it bind all the composition. The physical and chemical properties of this mineral block were characterized by characterization technique. Therefore, mineral block may be considered as an alternative to promote intensive use of agro-industrial byproduct and overcome nutritional constraints.